Mutagenic and cytotoxic effect of planifolin: A naphthopyranone dimer isolated from Paepalanthus planifolius - Varanda, Eliana Aparecida [UNESP]; Varella, S. D.; Rampazo, R. A.; Kitagawa, R. R.; Raddi, MSG; Vilegas, Wagner [UNESP]; dos Santos, L. C. (Elsevier B.V., 2006)
A naphthopyranone dimer, named planifolin, was isolated from a methylene chloride extract of the capitula of Paepalanthus planifolius Koern. The molecule (C31H26O10) appeared to be made up of two monomeric portions, semi-vioxanthin and paepalantine (an isocoumarin), linked by an ether bond, and it may possess several kinds of biological activity that can be related to its polyphenolic structure. Short-term tests that detect genetic damage can afford the information needed to evaluate carcinogenic risks of chemicals to humans. The Ames test, recommended for testing the mutagenicity of chemical compounds with potential pharmacological application, was used in the present study. The mutagenic activity was evaluated in Salmonella typhimurium strains TA100, TA98, TA102 and TA97a and the cytotoxic effect in McCoy cells. The in vitro cytotoxicity of planifolin to McCoy cells, tested in microculture with neutral red, showed a significant cytotoxic index (CI50) of 12.83 mu g/mL. Planifolin showed mutagenic activity for TA100, TA98 and TA97a. The results indicate that this new naphthopyranone dimer causes mutations by substitution and by addition and deletion of bases in the sequence of DNA. Moreover, its mutagenic potential was increased by metabolic activation. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: planifolin; mutagenicity; Salmonella typhimurium